Action of the Metalloproteinases in Gonadal Remodeling during Sex Reversal in the Sequential Hermaphroditism of the Teleostei Fish Synbranchus marmoratus (Synbranchiformes: Synbranchidae) - Mazzoni, Talita Sarah [UNESP]; Lo Nostro, Fabiana Laura; Antoneli, Fernanda Natalia; Quagio-Grassiotto, Irani [UNESP] (Mdpi, 2018)
Teleostei present great plasticity regarding sex change. During sex reversal, the whole gonad including the germinal epithelium undergoes significant changes, remodeling, and neoformation. However, there is no information on the changes that occur within the interstitial compartment. Considering the lack of information, especially on the role played by metalloproteinases (MMPs) in fish gonadal remodeling, the aim of this study was to evaluate the action of MMPs on gonads of sex reversed females of Synbranchus marmoratus, a fresh water protogynic diandric fish. Gonads were processed for light microscopy and blood samples were used for the determination of plasma sex steroid levels. During sex reversal, degeneration of the ovaries occurred and were gradually replaced by the germinal tissue of the male. The action of the MMPs induces significant changes in the interstitial compartment, allowing the reorganization of germinal epithelium. Leydig cells also showed an important role in female to male reversion. The gonadal transition coincides with changes in circulating sex steroid levels throughout sex reversion. The action of the MMPs, in the gonadal remodeling, especially on the basement membrane, is essential for the establishment of a new functional germinal epithelium.
Keywords: extracellular matrix; collagenase; protogynous diandric fish; germinal epithelium; gonad